Considerações sobre a devastação mãe-filha: elementos para uma clínica da adolescência feminina - Brunner, Isadora Lins Porto Dantas (2008)
This work deals with the question of the mother-daughter devastation. It intends to go deeper into what comes to be devastation, understood, at first, as the failure of the daughter in acceding to femininity owing to lived obstacles in the relation with her mother. From seeing girls in adolescence, it appeared the idea to investigate such question in a more attentive way. Thus, this research uses a work of the contemporaneous cinema in order to take advantage of the resources of this condenser of livings art. With the purpose of articulating the problematic of devastation to what Freud called civilization and Lacan, discourses , that is, to an economy of the accepted or prescript jouissances of the social bond, this investigation considers aspects related to both the capitalism of production in Freud s time and specially, the late capitalism or current capitalism of consume. It also elaborates questions related to adolescence which, due to its turbulence, is presented as a privileged moment to the devastation occurrence. In conclusion, it develops the idea which, in each woman s trajectory to her own constitution as unique, to identify herself and, at the same time, to get separated from her mother, not finding a signifier that says The Woman, the devastation is presented as a contingence that can become real or not happens. However, when it takes place, it implies a suffering to the subject to whom the clinic can t stay indifferent